The Role of Arts, Imagination & Creativity in Transformative Learning: What is Adult Education’s Responsibility in Facilitating this Learning? - Soni Simpson (Adult Education Research Conference, 2006)
In this session, we will explore how creativity and imagination can play a role in transformative learning as well as the role of adult education in this process. Themes regarding non-artists or “regular adults” reaching new meaning platforms with the aid of creative expression are emerging in current research
Keywords: Transformative Learning; Creative Expression; Imagination; Meaning-making